The roles of serum Th1, Th2, and Th17 cytokines in patients with chronic urticaria: a systematic review and meta-analysis - Xue, Jingwen; Sun, Chinghsuan; Shi, Mai; Li, Bingyu; Zhao, Yi (Frontiers in Allergy, 2025)
ObjectivesTo conduct a systematic review and meta-analysis to identify Th1-, Th2, and Th17 related serum biomarkers that reflect disease activity in chronic urticaria (CU), thereby enhancing the assessment of disease activity in both trials and clinical practice.MethodsSystematic searches of PubMed, EMBASE, and Web of Science were conducted through November 2024 to identify articles reporting the associations between CU and serum biomarkers. Serum Th1, Th2, and Th17 related biomarkers were identified in CU patients and correlated with disease severity and patient characteristics (ex. Age, sex, and comorbidities). The study quality was assessed using the National Heart, Lung, and Blood Institute Quality Assessment Tool for case-control studies. Meta-analysis was performed using the random-effects model with Hedges' g to pool standardized mean differences (SMDs). For meta-analysis, data were included for biomarkers reported in at least four studies with available means and standard deviations (SDs). Data reported as medians with ranges or interquartile ranges (IQRs) were evaluated for skewness. If the data were found to be significantly skewed, the means and SDs were not calculated. Conversely, if the data were not skewed, the means and SDs were estimated using validated methods.ResultsA total of 6,013 studies were screened, of which 50 were included, reporting 22 serum Th1, Th2, and Th17 related cytokines. Meta-analyses revealed significant pooled standardized mean differences (SMDs) for serum TNF-α and IL-17.ConclusionsSerum TNF-α and IL-17 levels are significantly increased in patients with CU compared to healthy age- and sex-matched controls. These findings have the potential to influence clinical guidelines for the diagnostic workup of CU to include testing the serum levels of TNF-α and IL-17.